Health-related quality of life and coping strategies adopted by COVID-19 survivors: A nationwide cross-sectional study in Bangladesh - Hossain, Mohammad Anwar; Shafin, Rubayet; Walton, Lori Maria; Raigangar, Veena; Jahid, Iqbal Kabir; Islam, Mir Raihanul (2022)
Intoduction: This study aims to investigate the health-related quality of life and coping strategies among COVID-19 survivors in Bangladesh. Methods: This is a cross-sectional study of 2198 adult, COVID-19 survivors living in Bangladesh. Data were collected from previously diagnosed COVID-19 participants (confirmed by an RT-PCR test) via door-to-door interviews in the eight different divisions in Bangladesh. For data collection, Bengali-translated Brief COPE inventory and WHO Brief Quality of Life (WHO-QoLBREF) questionnaires were used. The data collection period was from October 2020 to March 2021.